2019
DOI: 10.1016/j.prosdent.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life after prosthodontic treatment for patients with partial edentulism: A systematic review and meta-analysis

Abstract: TFDP and IFDP had short- and long-term positive effects on OHRQoL. RPDs positively affected OHRQoL in the short term. IFDP showed greater short-term improvement in OHRQoL than RPD and TFDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
89
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 53 publications
(47 reference statements)
6
89
0
17
Order By: Relevance
“…Two studies with a patient material comparable to ours comparing the patient‐reported effect between ISFP and FDP treatments also found that the OHIP‐14 score declined similar or insignificantly slightly more in the ISFP group than the FDP group . Two other studies and two reviews also found no difference in patient‐reported effect between the two treatments or slightly better short‐term effect of the ISFP …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Two studies with a patient material comparable to ours comparing the patient‐reported effect between ISFP and FDP treatments also found that the OHIP‐14 score declined similar or insignificantly slightly more in the ISFP group than the FDP group . Two other studies and two reviews also found no difference in patient‐reported effect between the two treatments or slightly better short‐term effect of the ISFP …”
Section: Discussionsupporting
confidence: 66%
“…The patient‐reported effect of both ISFP and FDP has been investigated separately in several studies, and both treatments have shown ability to improve OHRQoL . The few studies that have actually compared the patient‐reported effect between the two treatment modalities report similar effect for the two modalities .…”
Section: Introductionmentioning
confidence: 99%
“…Two recent reviews also looked at the effect and change in OHRQoL after treatment with different modalities for replacement of teeth. One concluded that not enough evidence was accessible to draw any final conclusions, whereas the other concluded that treatment with RDP have lower effect than fixed prostheses, especially in the long run . Our results might appear contradictory to this as the RDP groups seemingly had higher patient‐reported effect than the FDP group.…”
Section: Discussionmentioning
confidence: 56%
“…Even though it has been recommended to use more than one measure of patient‐reported effect, most other studies investigating the patient‐reported effect of oral rehabilitation have used one method only, most often being an OHRQoL questionnaire . A few studies have, however, included global ratings to estimate the important difference in OHIP‐score.…”
Section: Discussionmentioning
confidence: 99%
“…The ISC studies frequently reported outcome rates exceeding 95%. Meta-analyses found success rates of 96.7% to 97.5% for single-unit restorations and 92.5% to 93.6% for FPD restorations over six to seven years [8,9]. Others shows that both ISC and RCT have superior long-term survival compared with FPD [10 -12].…”
Section: Introductionmentioning
confidence: 99%